EXPLORING MOBILE- ASSISTED LANGUAGE LEARNING (MALL) AS A CATALYST FOR DIGITAL LITERACY AMONG DIGITAL NATIVE - Elga Romadhon, M Galuh (International Journal of Instructions and Language Studies, 2025)
This qualitative study is designed to explore how Gen Z undergraduate English literature students use mobile phones to learn the language and develop digital literacy. It shall collect descriptive data on how experiences are perceived with intensive interviews with five students using the studied technological means for learning actively. This research will therefore employ narrative analysis, accounting for the shared themes, personal tales, and shifting role of MALL in order to trace each participant's learning trajectory. This research focuses on recent trends among the Gen Z population regarding how MALL fosters student engagement in building confidence and developing digital competencies through such rapidly changing technological times. The general challenges experienced by the students will also come to light through this study and hence provide useful insights into pragmatic implications of the MALL usage. Discussing advantages and challenges in the given study contribute to enabling better strategies for integrating MALL into the classroom for teaching English Literature and providing digital literacy skills necessary for the 21st century in Gen Z students.